A series of copper-free ternary oxide catalysts ZnAlCex used for hydrogen production via dimethyl ether steam reforming - Zhang, Lijie; Meng, Ming; Wang, Xiaojing; Zhou, Shuang; Yang, Lijuan; Zhang, Tianyong; Zheng, Lirong; Zhang, Jing; Hu, Tiandou (Journal of power sources, 2014)
Ce-substituted ternary oxide catalysts ZnAlCex were prepared and employed in dimethyl ether steam reforming (DME SR) to produce hydrogen. XRD, XAFS (XANES & EXAFS), H2O-TPD, CH3OH-TPD and TPSR techniques were used for catalyst characterization. It is found that the catalytic performance of these catalysts is dependent on Ce content. The catalyst containing 20 wt% CeO2 exhibits the best catalytic performance. Its calculated TOF (0.034 s−1) is nearly three times to that of ZnAlO. The kinetic results reveal that the addition of 20 wt% CeO2 to ZnAlCex greatly decreases the apparent activation energy (Ea) of DME SR, due to the formation of new reaction sites such as Ce4+–O–Zn2+ linkages. XRD and EXAFS analyses indicate that Ce addition can not only decrease the crystallite size of ZnO and ZnAl2O4, but also tune the relative contents of them. The results of H2O-TPD and CH3OH-TPD show that Ce addition can lower H2 desorption temperature, which accounts well for the better catalytic performance of ZnAlCex. It is worth noting that the Zn-based catalysts display much lower CO selectivity than the Cu-based one, especially the Ce-substituted ZnAlCex. Start-off durability tests demonstrate that this series of catalysts also possess high catalytic stability. •Ce-substitution greatly improves the DME SR performance of ZnAlCex catalysts.•The optimized CeO2 content in ZnAlCex catalysts is 20% by weight.•The presence of Ce in ZnAlCex can enhance H2 desorption at lower temperature.•ZnAlCex catalysts exhibit much lower CO selectivity than Cu-based one.•The catalyst ZnAlCe0.2 shows very high catalytic stability even at 420 °C.